More-than-human relations on the third rock from the sun - LIM, Michelle Mei Ling (Institutional Knowledge at Singapore Management University, 2023)
The doomsday clock ticks close to the hour. Let's talk about privilege; let's talk about power! Come! says Rock, Come, every being, every creature, It is time to decide what will be in our future. We’ve been called to judge for Epoch Anthropocene, Better worlds depend on our powers to dream. What do we say on this Judgment Day? Enough of the systems that got us this way! What would it mean if the world could start over? Let's ask the mountain, the lichen, and the bird who's a loner.